Electrofluidodynamic technologies (EFDTs) for biomaterials and medical devices : principles and advances - Guarino, Vincenzo; Ambrosio, Luigi, 1955- (Woodhead Publishing series in biomaterials., 2018)
Electrofluidodynamic Technologies (EFDTs) for Biomaterials and Medical Devices: Principles and Advances focuses on the fundamentals of EFDTs - namely electrospinning, electrospraying and electrodynamic atomization - to develop active platforms made of synthetic or natural polymers for use in tissue engineering, restoration and therapeutic treatments. The first part of this book deals with main technological aspects of EFDTs, such as basic technologies and the role of process parameters. The second part addresses applications of EFDTs in biomedical fields, with chapters on their application in tissue engineering, molecular delivery and implantable devices. This book is a valuable resource for materials scientists, biomedical engineers and clinicians alike. Presents a complete picture of Electrofluidodynamic technologies and their use in biomedicineProvides a comprehensive, professional reference on the subject, covering materials processing, fabrication and the use of novel devices for tissue engineering and therapeuticsFocuses on technological advances, with an emphasis on studies and clinical trials